PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA VERENA MULTI FINANCE TBK CABANG PEKANBARU - Rosalina, Lamsiska; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Factors that affect the performance of employees, among others, career development and work motivation. The research was conducted on employees PT.Verena Multi Finance Tbk Branch Pekanbaru, the purpose of this study was to determine and analyze the influence of career development and work motivation on employee performance. The sample used in this study is 40 samples, this method of data collection using the questionnaire. The analysis technique used is a simple linear regression and multiple linear regression method used is descriptive analysis method, and multiple linear analysis method that produces output t test, F test, and test the determinant (R²). Processing data using SPSS 20.0 program. Based on the analysis performed can be explained that the development of a strong influence on employee performance, where as the higher work motivation it will affect employee performance improvement. And if the career development and work motivation to do together will affect the performance of employees.Keywords: career development,work motivation, employee performance